Best Answer

If 3a+5=5a+3, then:

3a+5 - 3a = 5a+3 - 3a

5=2a+3

5 - 3=2a+3 - 3

2=2a

a=1

Q: 3a plus 5 equals 5a plus 3?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

5a - 5 = 7 + 2a ( subtract 2a from both sides) 3a - 5 = 7 (add 5 to both sides) 3a = 12 ( divide both sides by 3) a = 4

7a + 4 = 5a + 7 7a = 5a + 3 2a = 3 a = 3/2

5a times 3a minus 8a = (5*3)*a2 - 8a = 15a2 - 8a

5a(a(a-5)+3)

9a+21 3(3a+7)

Related questions

Answer to: 5a + 1 = a - 3a = -1

13a - 6 + a = 5a + 3 + 3a 13a + a - 5a - 3a = 3 + 6 6a = 9 6a/6 = 9/6 a = 3/2

a + b + c = 180 b = 3a c = 5a Substituting the values of b and c into the first equation. a + 3a + 5a = 180 or 9a = 180 so that a = 20 then b = 3a = 3*20 = 60 and c = 5a = 5*20 = 100

-8a + 3a = (-8 + 3)a = (5)a = 5a

5a - 5 = 7 + 2a ( subtract 2a from both sides) 3a - 5 = 7 (add 5 to both sides) 3a = 12 ( divide both sides by 3) a = 4

7a + 4 = 5a + 7 7a = 5a + 3 2a = 3 a = 3/2

5a times 3a minus 8a = (5*3)*a2 - 8a = 15a2 - 8a

a = 3

It is not clear whether the question is 3a + 4a + 5a + 6a^3 which would be 12a + 6a^3 or 3a + 4a + 5a + (6a)^3 = 12a + 216a^3 or (3a + 4a + 5a + 6a)^3 = 5832*a^3 But none of these really require summation notation!

-7a+2a+9 is also -5a+9. -5a+9=24. -5a=15. a=-3.

3a2 - 16a + 5 = 3a2 - 15a - a + 5 = 3a(a -5) - 1(a -5) = (3a - 1)(a - 5)

In order to solve something, there needs to be an equation. If I have read your equation right you have: (a² - 4)/(2 + 6a) x (3 + 9a)/(a² + 5a + 6) This looks like it needs to be simplified. There are two fractions being multiplied, so multiply the numerators and denominators together, giving: (a² - 4)/(2 + 6a) x (3 + 9a)/(a² + 5a + 6) = ((a² - 4)(3 + 9a)) / ((2 + 6a)(a² + 5a + 6)) Now, simplify the polynomials to remove the squared terms and any common factors: a² - 4 = (a - 2)(a + 2) 2 + 6a = 2(1 + 3a) 3 + 9a = 3(1 + 3a) a² + 5a + 6 = (a + 3)(a + 2) Giving: ((a² - 4)(3 + 9a)) / ((2 + 6a)(a² + 5a + 6)) = ((a + 2)(a - 2)3((1 + 3a))/(2(1 + 3a)(a + 3)(a + 2)) This can now be simplified by cancelling out equivalent terms, giving: ((a + 2)(a - 2)3(1 + 3a))/(2(1 + 3a)(a + 3)(a + 2)) = ((a - 2)3) / (2(a+3)) = 3(a - 2) / 2(a + 3) = (3a - 6) / (2a + 6)